Medium and high spin structure in the 94Y isotope produced in fission induced by cold neutrons. (5th September 2017) - Iskra, Ł W; Fornal, B; Leoni, S; Bocchi, G; Blanc, A; Bottoni, S; Cieplicka-Oryńczak, N; Jentschel, M; Köster, U; Michelagnoli, C; Mutti, P; Soldner, T; et al.
Abstract: The level scheme of the neutron-rich 94 Y isotope has been extended up to the 5324 keV excitation energy. During the analysis, a structure above the previously known (5 + ) isomer, at 1202 keV, was extended by employing multifold gamma-ray coincidence relationships measured with the EXILL array. For some of the new states, the spin-parity assignment has been proposed on the basis of gamma angular correlations and shell-model considerations. The newly identified structure is characteristic of spherical or nearly spherical configurations and no evidence for new isomers and rotational patterns was found.